Oil prices and the developing countries: The evidence of the last decade - Graciela Chichilnisky (Intereconomics, 1985)
Many of the present difficulties of the world economy have been blamed on the two oil-price explosions of the 1970s. Professor Chichilnisky shows that, at least in the case of the oil-importing developing countries, the negative effects have been overestimated. In fact, in some respects the oil exporters among the developing countries fared worse than the oil importers.
Keywords: 330; Developing Countries